DNA-based doping and fabrication of PN diodes - Bai, Ruobing; Liu, Yihan; Zhang, Bomin; Chen, Beishan; Xiong, Feng; Liu, Haitao (Frontiers in Nanotechnology, 2024)
This paper reports the fabrication of silicon PN diode by using DNA nanostructure as the etching template for SiO2 and also as the n-dopant of Si. DNA nanotubes were deposited onto ptype silicon wafer that has a thermal SiO2 layer. The DNA nanotubes catalyze the etching of SiO2 by HF vapor to expose the underlying Si. The phosphate groups in the DNA nanotube were used as the doping source to locally n-dope the Si wafer to form vertical P-N junctions. Prototype PN diodes were fabricated and exhibited expected blockage behavior with a knee voltage of ca. 0.7 V.Our work highlights the potential of DNA nanotechnology in future fabrication of nanoelectronics.